2015
DOI: 10.1055/s-0035-1551567
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Atresia: Improved Outcome in High-Risk Groups Revisited

Abstract: Objectives Improved survival in infants with esophageal atresia (EA) with a birth weight < 1,500 g or a major cardiac anomaly has been reported when compared with the original Spitz classification proposed in 1994. Aim We reviewed outcome data for infants born over the last decade in our institution to update previously reported survival statistics. Materials and Methods The records of all neonates (n = 200) with a diagnosis of EA managed in a single institution between 2001 and 2011 were reviewed and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 14 publications
1
14
2
4
Order By: Relevance
“…27,[31][32][33][34] However, it has been suggested that birth weight is nowadays not an important factor as it was previously, although major cardiac anomalies are still of poor prognostic aspect. 35 In our report, leakage rate remained stable over time between 11 and 16%, suggesting that surgical variations do not have any substantial influence on this complication. Likewise, neither open nor thoracoscopic technique seems to markedly affect the rate of recurrent fistula.…”
Section: Discussionsupporting
confidence: 55%
“…27,[31][32][33][34] However, it has been suggested that birth weight is nowadays not an important factor as it was previously, although major cardiac anomalies are still of poor prognostic aspect. 35 In our report, leakage rate remained stable over time between 11 and 16%, suggesting that surgical variations do not have any substantial influence on this complication. Likewise, neither open nor thoracoscopic technique seems to markedly affect the rate of recurrent fistula.…”
Section: Discussionsupporting
confidence: 55%
“…The overall mortality following surgery for EA/TEF was low at 4.2% and appears within international results. 3,[9][10][11]28 In general, the postoperative mortality seems to be more reflective of a center's overall neonatal expertise rather than the operative management itself as recently demonstrated by a nationwide study of 3479 children with EA/TEF across the United States. 8 Because of its rarity and complex nature, EA/TEF represents one of the major therapeutic challenges not only in modern pediatric surgery but also for other specialties involved due to serious short-and long-term morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Today, improved survival of newborns with EA/TEF is likely related to multiple factors including advances in neonatal intensive care and anesthesia, refined surgical techniques, parenteral nutrition, and antibiotics. 11,12 However, early [13][14][15] and late [16][17][18] postoperative morbidities frequently occur after initial repair of EA/TEF despite excellent surgical and neonatal management, and can be associated with impaired outcomes. Early recognition and treatment of potential complications is therefore essential in order to prevent poor long-term results.…”
Section: Introductionmentioning
confidence: 99%
“…Tekanan saat relaksasi di seluruh esofagus secara signifikan lebih tinggi dari pasien normal dan tekanan pada spinkter esofagus distal berkurang. 2,14,15 Pada atresia esofagus juga terdapat kelainan pada trakea berupa berkurangnya kartilago trakea dan peningkatan panjang muskulus transversus pada dinding posterior trakea. Pada kondisi lanjut dapat menimbulkan trakeomalasia dengan kolaps trakea sekitar 1-2 cm dari fistula.…”
Section: Diskusiunclassified
“…Begitu juga dengan tidak adanya udara gaster, hal ini dapat ditemukan di kelainan lainnya. 1,10,15 Diagnosis postnatal atresia esofagus dapat dibuat ketika terjadi kesulitan atau ketidakmampuan selang nasogastrik atau orogastrik melewati esofagus. Normalnya kardiak lambung pada bayi terletak 17 cm dari gusi bayi, tetapi pada kasus atresia esofagus, selang berhenti ketika masuk sepanjang 10-12 cm.…”
Section: Artikel Asliunclassified